Recent Advances on Synthetic and Polysaccharide Adhesives for Biological Hemostatic Applications - Li, Dawei; Chen, Jing; Wang, Xing; Zhang, Mingming; Li, Chunlin; Zhou, Jin (Frontiers in Bioengineering and Biotechnology, 2020)
The formation of stable blood clots or hemostasis is essential to prevent major blood loss and death from excessive bleeding. However, the body’s own coagulation process is not able to timely accomplish hemostasis without the assistance of hemostatic agents. Conventional closure techniques, including suturing and stapling, have many disadvantages. They inflict additional damage on the tissue, elicit inflammatory responses and have a relatively long application time. Especially for the more demanding wounds, where fluids or gasses are to be sealed off, these techniques are often insufficient. Therefore, a large variety of tissue adhesives, sealants and hemostatic agents have been developed. From an overview of tissue adhesive materials from a polymer chemistry perspective, hemostatic materials are mainly divided into synthetic polymer and naturally-derived polysaccharide adhesives. This review provides an overview of synthetic and polysaccharide-based hemostatic agents that related to their clinical hemostatic applications. Although each type has its specific advantages, few have become standard in clinical practice. For now, the search for better adhering, stronger, easier applicable and cheaper adhesives continues and this review is intended as starting point and inspiration for future research effort to develop the next generation of hemostatic adhesives.